CYBERBULLYING POLICIES OF SOCIAL MEDIA COMPANIES - Milosevic, Tijana (AoIR Selected Papers of Internet Research, 2015)
Relying on theories of privatization of the digital public sphere and youth risks and opportunities online, this study addresses a gap in academic research about the role of social media companies in addressing cyberbullying, as one aspect of digital imaginary. It analyzes self-regulation mechanisms that social media companies have in place to intervene in existing and prevent future cyberbullying incidents on their platforms. These mechanisms include, but are not limited to, reporting and social reporting tools, blocking, filtering, geofencing as well as any forms of human or automated moderation systems such as supervised machine learning; or prevention-oriented tools like educational materials based on social-emotional learning research. Methodologically, this study conducts qualitative textual analysis of fourteen social media companies’ terms of service, corporate statements, blogs and other documents relevant for this issue; as well as twenty-seven in-depth interviews with the companies’ representatives, and the representatives of e-safety NGOs that work with these companies on cyberbullying policy design in the United States and European Union. The study seeks to analyze what is considered as an effective social media cyberbullying policy; what can be known about the relative effectiveness of self-regulatory effort and the implications for users’ civil liberties and child safety online.